Wkład profesorów Szkoły Głównej Wielkiego Księstwa Litewskiego w rozwój przyrodoznawstwa - Kamińska, Janina (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2021)
During the time of the Commission of National Education the former jezuite Academy of Vilnius was restructured and renamed Main School of the Grand Duchy of Lithuania. Its rector Marcin Poczobut (1728–1810) took care to make new enlightenment sciences and medicine available to the students. Emphasis was put especially on natural science, which comprised mineralogy, zoology and botany. There were, however, no specialists in Lithuania, so they had to be sought outside.The leading professors of this disciplines were the naturalist dr Jean Emmanuel Gilibert (1741–1814) and Johann Georg Adam Forster (1754–1794), naturalist and travel writer, who took part in James Cook’s (1728–1779) second journey to the Pacific. They helped create the botanical garden and the cabinet of natural history. They also contributed to the first geological, botanical and zoological studies in Lithuania, publishing the results of their research.The largest contribution to the development of natural science was brought by Stanisław Bonifacy Jundziłł (1761–1847) – Forster’s student, who directed the Natural History Department, took care of the garden and cabinet as well as published his research.Showing a full picture of the natural sciences in Vilnius calls for a further archive research. Emphasis should be put on the analysis of the contacts of the Main School’s professors with academic centres in Europe.
Keywords: Main School of the Grand Duchy of Lithuania; natural sciences; Jean Emmanuel Gilibert; Johann Georg Adam Forster; Stanisław Bonifacy Jundziłł